OFFICE BUILDING DESIGN WITH A METAPHORICAL APPROACH IN PULO GADUNG – EAST JAKARTA PERANCANGAN GEDUNG PERKANTORAN DENGAN PENDEKATAN METAFORA - Gerie Munggaran; Elly Cornelies; RizKi Hambali (Universitas PGRI Sumatera Barat, 2024)
ABSTRACTEtymologically, metaphorical terminology is formed through the combination of two Greek words, namely